3(1-x)-5(x+2)=1-4x

Simple and best practice solution for 3(1-x)-5(x+2)=1-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-x)-5(x+2)=1-4x equation:


3(1-x)-5(x+2)=1-4x

We simplify the equation to the form, which is simple to understand
3(1-x)-5(x+2)=1-4x

Reorder the terms in parentheses
+(+3-3x)-5*(x+2)=1-4x

Remove unnecessary parentheses
+3-3x-5+*(+x+2+)=+1-4x

Reorder the terms in parentheses
+3-3x+(-5x-10)=1-4x

Remove unnecessary parentheses
+3-3x-5x-10=+1-4x

We move all terms containing x to the left and all other terms to the right.
-3x-5x+4x=+1-3+10

We simplify left and right side of the equation.
-4x=+8

We divide both sides of the equation by -4 to get x.
x=-2

See similar equations:

| 16r-18=126 | | -12-10x=2 | | 4(2x+3)=1 | | 3x-4y=7forx | | 4x^2-14x-8=9 | | 8x-7+3x=7x-1 | | 3m-3= | | 30x^2-10x=0 | | 2b+b+3b+10+3b-19=360 | | z^2-7x+12=0 | | -2x/-3=4 | | (2x^2)/(x^2+x-12)-(x-1)/(x-4)=(x+6)/(x-3) | | 3a+15+ab+5b=0 | | q+14=(q+7) | | x+32=y-7 | | (4x+15)=(2x+65) | | 36x^9-16x^5-12x^3=0 | | x/(x-1)+1/(x+1)=(x^2+1)/(x^2-1) | | 24x^4+27x^2=0 | | (228*3.5)/((1-x)*228)+(x*3.5)=14 | | -5x+10=-74+7x | | (228*3.5)/((1-x)*228)+(x*3.5) | | -6+4x=x-21 | | X-14=5y | | (6x-4)/(9x-1)=(2x+5)/(3x+10) | | -c+4c=8c-c | | 7t=80+5t | | 4+7x=-x+52 | | -8x+7=49 | | 4(2b-6)+11=8b-12 | | (8*x)^2/3*(9*x^3)^1/2 | | 7y-14=3y+11+2y |

Equations solver categories